Revisiting polychlorinated biphenyls enriching in human and disrupting of thyroid hormone receptor β1 - Qiao Wang; Junsong Bao; Yuhao Fan; Junjie Jiang; Ying Wang; Limei Chen; Jun Jin (Emerging Contaminants)
Polychlorinated biphenyls (PCBs) are persistent organic pollutants renowned for their bioaccumation and toxicity. Although PCBs production and use were banned worldwide decades ago, PCBs still pose a health risk due to their environmental persistence and unintentional production. In this report, PCB concentrations and temporal trends in serum from residents of urban areas in eastern China is investigated. The endocrine-disrupting potentials of PCBs are also investigated, particularly effects on thyroid hormone receptors. Through analysis of five years of data, results indicated that dioxin-like PCBs and congener PCB209 concentrations maintained low and had no marked temporal trends, but that the indicator PCBs and particularly PCB52, PCB153, and PCB180 concentrations increased. Furthermore, to evaluate binding of PCBs to the thyroid hormone receptor TRβ1, molecular docking simulations are performed. It is found that the PCBs of PCB28, PCB52, and PCB153 can interfere with triiodothyronine binding to TRβ1, which are comparable to the effects of the polybrominated biphenyl BB-153, a known thyroid function disruptor. What's more, the PCB180 binds to TRβ1 more strongly than that of BB-153. Our results indicated that a continuously monitoring of human exposures to PCB28, PCB52, PCB153, PCB180, and a detailed assessment of thyroid function interference is necessary.